Jansenella griffithiana (M?ll. Hal.) Bor (Gramineae/Poaceae): a new record for Thailand - Teerawatnanon, Atchara; Hodkinson, Trevor R. (Thai Forest Bulletin (Botany), 2014)
We report that Jansenella griffithiana ( M ll. Hal.) Bor is a new genus and species record for Thailand based on collections from Ranong Province by A.F.G. Kerr in 1929 and by A. Teerawatananon & S. Sungkaew in 2001. We also discuss its typification and designate a lectotype.